Current problems and solutions for the protection of water resources - B.B. Umarov; A.U.Anvarov; J.M.Abdumajidov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article analyzes in detail the importance of water resources for humanity and nature, the problems they face today - pollution, depletion, and improper management. Effective water resource management, water-saving technologies, and ways to increase environmental awareness will be considered. It also provides information on water conservation policies and sustainable development strategies implemented at the global and local levels.